Membangun Kerja Sama dengan Sekolah Nonformal dalam Menyediakan Informasi Edukatif bagi Orang Tua Anak - Icam Sutisna; Yenti Juniari; Sri Indrawati Zakaria; Sinta Abdullah; Fika J. Labanu (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
This activity aims to build collaboration with non-formal schools in providing educational information for parents through brochures. Information about the services, programs, and advantages of non-formal schools is often not optimally conveyed to parents, so simple but effective media is needed to broaden their understanding. In this activity, the team collaborated with non-formal schools to collect accurate data on the institution's profile, educational programs, service schedules, and other supporting information. The data was then compiled into an informative brochure that was designed to be attractive, concise, and easy to understand. The completed brochure was socialized and distributed directly to parents as a form of dissemination of educational information. The results of the activity showed that the use of the brochure was able to help parents gain a clearer understanding of available non-formal education services, thus becoming a consideration in supporting their children's learning needs. This activity also strengthened the collaborative relationship between program organizers and non-formal schools in supporting the provision of educational information for families.